O bioma Pampa nos anos iniciais do ensino fundamental: abordagens e percepções - Pinto, Luiza Frigo (2019)
Science teaching in the early school years contributes to the understanding of scientific subjects, among which those related to the environment can be highlighted. Through discussion and construction of new knowledge, it is possible for the student to realize the importance of awareness and preservation of local ecosystems. In this sense, knowledge about the Pampa biome within the school context may enable students to identify their natural environment, reduce environmental problems, landscape de-characterization and natural balance. Therefore, the present research aimed to investigate the perception of students and teachers of elementary school about the Pampa biome, as well as the accomplishment of a diagnosis on the subject approach by the teachers and the didactic books as indicated in PNLD 2016 for the initial school years. The decision to evaluate these books was made due to their association in the formative process as being pedagogical resources largely utilized by the teachers. The methodological approach was based on qualitative and quantitative analysis, being carried out with 5th grade students and all teachers working in the initial school years of three state public schools. As results, it was verified that the students have comprehensive perceptions about the natural environment describing the Pampa biome from general elements. Regarding the teachers' approach on the Pampa biome subjects, it was verified that it is simplified and not very contextual. It is worth noting the use of different methodological resources by the teachers, but the textbook is still the most utilized material. Thus, in the analysis of the indicated books by PNLD 2016 for the initial school years, one can observe several collections available for teachers to select, but only five collections presented the theme contextualization. The contextualization of this theme with the students’ daily life can contribute significantly to their learning, making it necessary to update the teachers' teaching methods so that the children are made aware of the importance of preserving local ecosystems.